EL UNIVERSO APP RADIOFÓNICO. ESTUDIO COMPARADO DE RADIO ESPAÑA FM Y RADIO NACIONAL DE ESPAÑA - Lda. Marta HERNADO LERA, (Fonseca, Journal of Communication, 2023)
Mobile applications are being an important revolution for users and also for radio listeners. In Spain we can find several examples of them which allow us to listen the radio through different radio stations or on-demand content. Smartphones and tablets are starting to be the axis of a new market which has to adapt its contents to this kind of devices. This piece wants to show the big picture regarding the features and content of different radio mobile applications, taking Radio España FM and Radio Nacional de España en Directo as object of study. Through them we will discover their main advantages and disadvantages, and use them as a starting point and to reflect on the aspects they have developed or should provide to the radio media on mobile applications.